2007
DOI: 10.1073/pnas.0611170104
|View full text |Cite
|
Sign up to set email alerts
|

Molecular determinants for the interaction between AMPA receptors and the clathrin adaptor complex AP-2

Abstract: ␣-Amino-3-hydroxy-5-methylisoxazole-4-propionic acid (AMPA)-type glutamate receptors undergo constitutive and ligand-induced internalization that requires dynamin and the clathrin adaptor complex AP-2. We report here that an atypical basic motif within the cytoplasmic tails of AMPA-type glutamate receptors directly associates with 2-adaptin by a mechanism similar to the recognition of the presynaptic vesicle protein synaptotagmin 1 by AP-2. A synaptotagmin 1-derived AP-2 binding peptide competes the interactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
72
1
3

Year Published

2008
2008
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(76 citation statements)
references
References 27 publications
0
72
1
3
Order By: Relevance
“…Thus, the binding of clathrin adaptor AP-2 to the cargo containing AMPA receptors is a key final step in executing AMPA receptor endocytosis during LTD. Although the m2 subunit of AP-2 was shown previously to bind directly to the membrane proximal region (MPR) of GluA2/A3 in vitro, in a manner dependent on GluA2's arginine 845 (R845) 6 , it has been unclear whether and how this process is regulated by neuronal activity. Here we showed that STG bound directly to m2 and enhanced the formation of a tripartite complex consisting of the AMPA receptor, STG and m2.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, the binding of clathrin adaptor AP-2 to the cargo containing AMPA receptors is a key final step in executing AMPA receptor endocytosis during LTD. Although the m2 subunit of AP-2 was shown previously to bind directly to the membrane proximal region (MPR) of GluA2/A3 in vitro, in a manner dependent on GluA2's arginine 845 (R845) 6 , it has been unclear whether and how this process is regulated by neuronal activity. Here we showed that STG bound directly to m2 and enhanced the formation of a tripartite complex consisting of the AMPA receptor, STG and m2.…”
Section: Discussionmentioning
confidence: 99%
“…S14a). This is probably because of the different experimental conditions used; Kastning et al 6 carried out a pull-down assay using a GST-tagged MPR of GluA2 and a recombinant m2, which was prepared by in vitro transcription and translation, whereas we performed a co-immunoprecipitation assay using full-length GluA2 and m2 after solubilizing membranes. Thus, a small difference in the m2-GluA2 wt and m2-GluA2 R845A interactions may not have been detected in our assay.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both constitutive and regulated AMPA receptor endocytosis were shown to be dependent on clathrin, the clathrin adaptors, and dynamin (3,(5)(6)(7)(8)(9). Thus, clathrin-mediated endocytosis, a process known to play a fundamental role in the recycling of synaptic vesicles (10,11), also has a critical role postsynaptically, although the flux of endocytic traffic is much more intense presynaptically.…”
mentioning
confidence: 99%
“…Thus, clathrin-mediated endocytosis, a process known to play a fundamental role in the recycling of synaptic vesicles (10, 11), also has a critical role postsynaptically, although the flux of endocytic traffic is much more intense presynaptically. Accordingly, a growing number of components of the clathrin-dependent endocytic machinery of the presynapse were reported, by either morphological or functional studies, to be present also at the postsynapse (8,9,12,13). One protein that is expressed at high levels in the nervous system and is concentrated in nerve terminals, where it has an important role in the clathrin-dependent recycling of synaptic vesicles, is synaptojanin 1 (SJ1) (14-17).…”
mentioning
confidence: 99%